EFEKTIVITAS PEMBELAJARAN MATEMATIKA MELALUI RECIPROCAL TEACHING PADA SISWA SMP HANG TUAH MAKASSAR - Rahmawati Rahmawati (Universitas Sulawesi Barat, 2018)
This study is a pre-experimental research that aims to determine the effectiveness of mathematics learning through the application of reciprocal teaching models in class IX students of SMP Hang Tuah in the academic year of 2017/2018. This study refers to four criteria of learning effectiveness, namely the achievement of classical learning completeness and improvement of learning outcomes grouped into learning outcomes, student activities related to learning activities, as well as students' positive response to learning implementation with reciprocal teaching models. The research design used was One Group Pretest-Posttest Design. The sample in this study were students of class IX.A Hang Tuah as many as 31 people as a trial class to apply the reciprocal teaching model. Data collection techniques used were observation techniques for learning achievement, learning outcome tests, observation techniques for student activities, and student response questionnaires. Research results show that (1) learning outcomes are in the medium category with an average score of 82.22 and a standard deviation of 8.64; (2) The average percentage of student activity frequency is 83.24 in the active category; (3) the ability of teachers to manage learning has increased, and is in the category of implementation with a score of 3.20; (4) student response to reciprocal teaching learning is 83.19%; and (5) hypothesis testing p-value 0,000 <0,05 = Î±, then H1 is accepted.